Dampak Sosial Peternakan Ayam Layer (Petelur) Terhadap Masyarakat Desa Tambakrejo Kecamatan Sumbergempol Kabupaten Tulungagung - Silvia Unsyatul Salsabila; Bagus Setiawan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The background to this research is due to the response of the public who feel disturbed by the existence of this layer chicken farming business due to the strong smell of farm waste, the presence of large numbers of fly insects and the noise coming from the breeder's cage. The focus of this research is what the community's response is to the existence of a layer chicken farm in Tambakrejo Village, Sumbergempol District, Tulungagung Regency and what the social impact of the community is with the existence of a layer chicken farm in Tambakrejo Village, Sumbergempol District, Tulungagung Regency. The aim of this research is to find out what the community's response is to the layer chicken farming business in Tambakrejo Village, Sumbergempol District, Tulungagung Regency. To find out what social impacts are felt by the community towards the layer chicken farming business in Tambakrejo Village, Sumbergempol District, Tulungagung Regency. This research uses descriptive qualitative methods with data collection techniques carried out by observation, interviews and documentation. The research location was carried out in Tambakrejo Village with the research subjects being the people of Tambakrejo Village whose houses were close to a layer chicken farm. The results of this research show that the responses given by the community are positive and negative. The community's positive response is that the community supports the existence of this farm. The negative response given by the community was that the community objected to the existence of this livestock business by giving responses that were indifferent and less concerned. The social impact felt by the community with the existence of a layer chicken farm in Tambakrejo Village, Sumbergempol District, Tulungagung Regency, is seen from a negative aspect. The community feels disturbed by the strong smell that comes from the manure of the layer chicken farm. Apart from that, flies coming to people's homes also make people feel uncomfortable because of the large number of flies. The community also complains about the water they use every day because the water digging is close to the farm, which has an impact on the smell of the water in the digging. Viewed from a positive aspect, people can easily buy or order eggs from breeders at much cheaper prices, besides that breeder owners often distribute eggs to local communities, especially during the month of Ramadan.